Mesopotamian Eye Disease Texts : The Nineveh Treatise. - Geller, Markham J.; Panayotov, Strahil V. (Boston : Walter de Gruyter GmbH, 2020)
Franz Köcher's magnum opus on Babylonian and Assyrian medicine, which was envisioned to include cuneiform copies, translations, and commentary, was unfinished at his death in 2002 with six volumes of cuneiform copies accompanied by brief introductory comments and citation of parallels and duplicates. Publication of the series is being resumed, under the editorship of Robert Biggs and Marten Stol. The new volumes include full translations and philological commentary, thus making Babylonian and Assyrian medical texts accessible to historians of ancient medicine in up-to-date studies.
Intro -- Acknowledgments -- Table of Contents -- Preface -- 1. Overview of Cuneiform Eye Disease Texts (Panayotov) -- 2. Introduction: Eye Disease in Mesopotamia (Geller) -- I. The Nineveh Manuscripts of Chapter One (IGI 1) -- Edition of IGI 1 -- II. The Nineveh Manuscripts of Chapter Two (IGI 2) -- Edition of IGI 2 -- III. The Nineveh Manuscripts of Chapter Three (IGI 3) -- Edition of IGI 3 -- IV. Additional texts from Nineveh -- V. From the Nineveh UGU treatise (BAM 480, 482) -- VI. Diagnostic Medical Omens Concerned with Sick Eyes (Diagnostic Handbook, Sakikkû Chapter 5) by Eric Schmidtchen -- Notes -- Glossaries and Logograms with Cuneiform Signs -- Abbreviations and Literature -- Indices -- Plates.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books